2003
DOI: 10.2334/josnusd.45.39
|View full text |Cite
|
Sign up to set email alerts
|

Rare lesions of the oral cavity: case report of an actinomycotic lesion limited to the gingiva

Abstract: Actinomycosis is an infectious disease that frequently has chronic granulomatous and suppurative lesions caused by saprophytic Actinomyces species. Although cervicofacial actinomycosis is known to be the most common type, intraorally and periodontally types occur rarely in a localized fashion. The present case reports on an adult periodontitis patient with a diffuse and atypic actinomycotic lesion which was limited to the gingiva and had an abscess formation, a large desquamation and subsequent exposure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…In case 2, granulomatous and ulcerative changes associated with a mucocele might have been a trigger of infection. Our review of the literature demonstrated that two cases had dental problems (6,12), while one case each had oral candidosis (9), a peculiar dental habit (13), and poor oral hygiene (14), respectively. A diagnosis of actinomycosis has typically been made based on bacterial culture tests.…”
Section: Discussionmentioning
confidence: 96%
“…In case 2, granulomatous and ulcerative changes associated with a mucocele might have been a trigger of infection. Our review of the literature demonstrated that two cases had dental problems (6,12), while one case each had oral candidosis (9), a peculiar dental habit (13), and poor oral hygiene (14), respectively. A diagnosis of actinomycosis has typically been made based on bacterial culture tests.…”
Section: Discussionmentioning
confidence: 96%
“…[3] The bacteria while not causing any pathology on the surface of the mucosal tissue, in cases where the integrity of the tissue is destructed may cause infection. Actinomycotic lesions usually occur following a dental infection or oromaxillofacial trauma.…”
Section: Discussionmentioning
confidence: 99%
“…It rarely causes disease (5). Actinomycosis may affect the cervicofacial, mediastinal, abdominal or pelvic regions (1,(6)(7)(8)(9)(10). The main step in the pathogenesis of actinomycosis is interruption of the mucocutaneus barriers leading to suppuration and abscess formation.…”
Section: Discussionmentioning
confidence: 99%